EFFECT OF DEVELOPMENT OF INDUSTRIAL TRANSPORTATION AND AGLOMERATION SECTORS ON ACEH ECONOMIC GROWTH - Reza Putra; Abd. Jamal; Eddy Gunawan (Syiah Kuala University, 2018)
AbstractThis study aims to determine the development ofthe transportation sector and industrial agglomerationtowards economic growth in Aceh Province. This studyuses data regression analysis method of Fixed Effectand White cross section Panels. Panel Data TestResults show that of the 6 variables, there are twovariables that show a negative relationship to economicgrowth, namely Capital Expenditure (BM) and RoadLength PerKapita (JPK), while 4 other variables showa positive relationship, namely the Index ofSpecialization (IS), Gross Fixed Capital Formation(PMTB), Road Length (PJL) and Average SchoolDuration (RLS). Test results also show that there aresignificant variables, namely the variable Gross FixedCapital Formation (PMTB) and Capital Expenditures(BM), and the non-significant multiple variables,namely the Specialization Index (IS), Average SchoolLength (RLS), Road Length (PJL) and Distance perCapita variable (JPK). To increase the economicgrowth of the government so that the transportationsector become one of the priorities, to facilitate themobility of goods and services in the region, as well asone way to create agglomeration, besides that thegovernment must also improve aspects as capital ineconomic growth and improvement of agglomeration inthe regions